2014
DOI: 10.1111/1469-0691.12477
|View full text |Cite
|
Sign up to set email alerts
|

Web-based participatory surveillance of infectious diseases: the Influenzanet participatory surveillance experience

Abstract: To overcome the limitations of the state-of-the-art influenza surveillance systems in Europe, we established in 2008 a European-wide consortium aimed at introducing an innovative information and communication technology approach for a web-based surveillance system across different European countries, called Influenzanet. The system, based on earlier efforts in The Netherlands and Portugal, works with the participation of the population in each country to collect real-time information on the distribution of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
153
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(155 citation statements)
references
References 10 publications
2
153
0
Order By: Relevance
“…FluNearYou [645,646], and InfluenzaNet [647,648] are two examples. The first platform engages individuals living in USA or Canada.…”
Section: Participatory Platforms For Digital Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…FluNearYou [645,646], and InfluenzaNet [647,648] are two examples. The first platform engages individuals living in USA or Canada.…”
Section: Participatory Platforms For Digital Surveillancementioning
confidence: 99%
“…In other words, the two platforms are systems for digital surveillance. Remarkably, several studies have shown that the ILI incidence estimated using these platforms is highly correlated with the classic ILI surveillance data [646,648,649]. With minimal participation from the subscribed users they allow to overcome several limitations of the classic systems.…”
Section: Participatory Platforms For Digital Surveillancementioning
confidence: 99%
“…5 Media reports of case numbers and deaths contributed to a distorted view of severity and political pressure for robust control measures. Attempts were made to identify community case numbers through prospective internet surveys (Europe) 6,7 or retrospective telephone surveys (USA). 8,9 These helped to provide better denominator estimates for calculation of CFR.…”
Section: Fundingmentioning
confidence: 99%
“…We are at the dawn of the digital revolution in epidemiology [7,8]. The new approach allows for the early detection of disease outbreaks [62], the real time monitoring of the evolution of a disease with an incredible geographical granularity [63][64][65], the access to health related behaviors, practices and sentiments at large scales [66,67], inform data-driven epidemic models [68,69], and development of statistical based models with prediction power [67,[70][71][72][73][74][75][76][77][78].…”
Section: Digital Epidemiologymentioning
confidence: 99%
“…In active data collection users are asked to share their health status using apps and web-based platforms [79]. Examples are influenzanet that is available in different European countries [64], and Flu near you in the USA [65] that engage tens of thousands of users that together provide the information necessary for the creation of interactive maps of ILI in almost real time. In passive data collection, instead, information about individuals health status is mined from other available sources that do not require the active participation of users.…”
Section: Digital Epidemiologymentioning
confidence: 99%